Social determinants of oral health in migrants at the Spanish border - Martín Hernández, Juan; Barbero Navarro, Ignacio; Rodríguez Menacho, Diego; Villalva Hernández, Paloma; Barrera Mora, Jose María; Ribas-Pérez, David; Castaño Séiquer, Antonio (Frontiers in Public Health, 2025)
BackgroundHealth equity, particularly in oral health, remains a challenge for socially excluded populations such as migrants. This study investigates the oral health status and associated social determinants of health among adult immigrants residing at the Temporary Stay Center for Immigrants (CETI) in Melilla, Spain.MethodsA cross-sectional study was conducted in March 2024 involving 128 adult CETI residents. Data collection included standardized oral examinations following WHO guidelines and structured questionnaires assessing sociodemographic variables, health habits, and dental care history. Statistical analyses were performed using SPSS 29.0, with significance set at p < 0.05.ResultsThe sample was predominantly Latin American (80.5%) and male (67.2%), with a mean age of 34.85 years. While most participants reported good oral hygiene habits, 67.2% were partially edentulous, and the mean Decayed, Missing, Filled, Teeth (DMFT) index was 9.73—higher than national averages. Only 9.4% used dental prostheses. Significant differences were observed between Latin American and African subgroups regarding age distribution, oral hygiene habits, and access to dental care.ConclusionMigrant populations at CETI face substantial oral health challenges and disparities linked to origin, education, and access to care. Ongoing epidemiological monitoring is essential to inform tailored, equity-oriented public health interventions that address the dynamic needs of these populations.